Smart metering application for power efficiency studies - Tudoran, Cristian; Albert, Stefan; N. Dadarlat, Dorin; Tripon, Carmen; Dan Anghel, Sorin (International Journal of Engineering and Technology, 2015)
Improving the energy efficiency of our Institute’s data center is an ambitious challenge for our research teams. Understanding how the energy is consumed in each segment of the system becomes fundamental in order to minimize the overall energy consumed by the system itself. In this paper, we propose an experimentally–driven approach to develop a simple and accurate power consumption and temperature monitoring system. In this work we focused our attention on the monitoring, measurement of the energy consumption patterns of our data center system, at INCDTIM Cluj-Napoca, Romania.